Ultralight Layer‐by‐Layer Self‐Assembled MoS2‐Polymer Modified Separator for Simultaneously Trapping Polysulfides and Suppressing Lithium Dendrites. Issue 35 (23rd October 2018) - Wu, Jingyi; Zeng, Hongxia; Li, Xiongwei; Xiang, Xiao; Liao, Yonggui; Xue, Zhigang; Ye, Yunsheng; Xie, Xiaolin
Abstract: Polysulfide shuttling and uncontrollable lithium dendrite growth have hampered the application of lithium–sulfur (Li–S) batteries. Although various materials have been utilized to overcome these obstacles, simple and scalable methods are still needed for Li–S battery commercialization. It is shown for the first time that the layer‐by‐layer (LbL) self‐assembly of 2D nanomaterials can be used to controllably fabricate multifunctional separators that simultaneously trap polysulfides and suppress lithium dendrite growth. The double‐sided "nanobrick wall" structure, constructed by MoS2 /poly(diallyl dimethyl ammonium chloride) hybrid in conjunction with poly(acrylic acid) (PAA), provides a physical shield against polysulfides and the chemical adsorption of such species by MoS2 and PAA. At the same time, the robust and Li‐ion conducting MoS2 layers strengthen the separator and regulate Li deposition, thereby effectively suppressing Li dendrite formation. As a result, a simple sulfur cathode battery with an ultralight separator coating (0.10 mg cm −2 ) is able to achieve an outstanding cycle stability with a capacity decay as low as 0.029% per cycle over 2000 cycles and a reversible areal capacity ≈2.0 mAh cm −2 at 1 C. The proposed LbL approach opens the door to the simple, scalable, and economic fabrication of advanced functional separators for use in the real world. Abstract : An ultralight MoS2 ‐polymer modified separator is fabricated by simple and scalable layer‐by‐layer self‐assembly. The "nanobrick‐wall" structure allows for the physical and chemical dual confinements of polysulfides, while the mechanically robust and Li + conductive multilayers effectively suppress lithium dendrite growth, thereby enabling the production of high performance Li–S batteries with remarkable cycle stabilities and long cycle lives.